MENGHITUNG KUADRAT DENGAN MENGGUNAKAN JARI PADA PEMBELAJARAN MATEMATIKA PAKET B - Muhammad Fajar Auliya (Jurnal Ilmiah Visi, 2009)
Mathematics is a difficult and dull subject for most of the students in formal education and non-formal eduaction. Many students are not interested to study this subject and find hard to understand. Meanwhile mathematics is much used in the other subjects and needed to improve the student’s intellectual skill. This article introduces an innovative technique to overcome the students’s difficulties in counting quadrate in mathematics by using fingers which is very practical and easy to use. Based on the experience, this technique can successful improve the learning achievement of Package B students and motivate them to learn mthematics.